2020
DOI: 10.1039/d0cp03847d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in the BMIM PF6/acetonitrile mixtures observed by femtosecond optical Kerr effect and molecular dynamics simulations

Abstract: We have performed the measurements of the optical Kerr effect signal time evolution up to 4 ns for a mixture of 1-alkyl-3-methyl-imidazolium hexafluorophosphate (BMIM PF6 ) ionic liquid and acetonitrile...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Indeed, in our recent optical Kerr effect study of a similar BmimPF 6 –ACN mixture (bulk solvent without the dye), we showed that admixing the IL to acetonitrile results in a significant slowdown of the mixture dynamics. We observed that already at X IL = 0.05, the slowest relaxation time is 18 ps and grows to 1.6 ns for the pure IL . In the case of systems with the dye, these relaxation times might differ in the cybotactic region compared to the bulk; however, they clearly show that solvation can be involved in τ 3 .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Indeed, in our recent optical Kerr effect study of a similar BmimPF 6 –ACN mixture (bulk solvent without the dye), we showed that admixing the IL to acetonitrile results in a significant slowdown of the mixture dynamics. We observed that already at X IL = 0.05, the slowest relaxation time is 18 ps and grows to 1.6 ns for the pure IL . In the case of systems with the dye, these relaxation times might differ in the cybotactic region compared to the bulk; however, they clearly show that solvation can be involved in τ 3 .…”
Section: Resultsmentioning
confidence: 75%
“…We observed that already at X IL = 0.05, the slowest relaxation time is 18 ps and grows to 1.6 ns for the pure IL. 65 In the case of systems with the dye, these relaxation times might differ in the cybotactic region compared to the bulk; however, they clearly show that solvation can be involved in τ 3 . In our case, even for the pure IL, we cannot see any evidence of solvation in the DAS associated with τ 4 , while it is clearly observed for τ 3 for the pure IL and all the mixtures.…”
Section: Discussion Of Four Global-analysis Time Constantsmentioning
confidence: 97%
“…Lastly, τ 4 can be attributed to the decay process of the charge transfer (CT) excited state. Furthermore, considering the presence of very slow solvation dynamics time components (especially in pure ILs and at higher X IL mixtures) found in previous studies, , we cannot discount the possibility of the solvation process contributing to both τ 3 and τ 4 as well.…”
Section: Resultsmentioning
confidence: 76%
“…However, in essence, all of the global analysis time components can be viewed as mixed-time components, incorporating multiple excited state processes. For instance, both τ 1 and τ 2 may involve solvation dynamics ,, alongside intramolecular vibrational relaxation (IVR), dye aggregation, and the ultrafast decay of the locally excited (LE)/Franck–Condon state, while τ 3 may primarily involve excited state vibrational relaxation and ultrafast twisting. Lastly, τ 4 can be attributed to the decay process of the charge transfer (CT) excited state.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that already at XIL = 0.05, the slowest relaxation time is 18 ps and grows to 1.6 ns for pure IL. 65 In the case of systems with the dye, these relaxation times might differ in the cybotactic region compared to the bulk; however, they clearly show that solvation can be involved in 3 . In our case even for pure IL we cannot see any evidence of solvation in the DAS associated with 4 , while it is clearly observed for 3 for pure IL and all the mixtures.…”
Section: Discussion Of Four Global Analysis Time Constantsmentioning
confidence: 98%